A framework for addressing the interconnectedness of early warning to action and finance to strengthen multiscale institutional responses to climate shocks and disasters - Emmanuel M.N.A.N. Attoh; Giriraj Amarnath (Climate Risk Management)
Early warning systems (EWS) inform decision making and planning in response to climate shocks and catastrophic disasters. However, the current disaster response mechanism falls short due to the fragmented warning, action, and finance systems, coupled with inadequate institutional collaboration, coordination and inclusive engagement for effective anticipatory action. This study addresses this challenge by introducing an Early Warning, Action and Finance (AWARE) platform to promote anticipatory action through multistakeholder engagement. Data from literature reviews, expert surveys, and stakeholder workshops in Senegal, Zambia and Sri Lanka helped identify the platform’s needs and priorities. The study draws upon theories of technological frames, interpretative flexibility, boundary objects, social learning, collaborative governance and adaptive co-management to conceptualize a framework for AWARE. Results demonstrate the potential of AWARE as a boundary object that fosters social engagement, active involvement, open communication, collaboration, and shared commitment to safeguarding lives and livelihoods. Analysis of technological frames and interpretative flexibility underscores the role of social learning in shaping the design and user features that promote multiscale institutional responses to disasters. AWARE aligns with the priorities of the Sendai Framework and emphasizes system thinking, co-production of knowledge, and the need for context-specific solutions to enhance anticipatory action. Recognizing the limitations of one-size-fits-all EWS, the AWARE framework acknowledges contextual factors as barriers to implementation. The study underscores the importance of integrated EWS and collaborative efforts to overcome implementation barriers and improve anticipatory action outcomes.